The 'best small nation navy in the world'? The twenty-first century Royal New Zealand Navy. Issue 3 (2nd July 2016) - Paget, Steven
ABSTRACT: The Royal New Zealand Navy (RNZN) has set itself the admirable goal of being the 'best small nation navy in the world'. As the RNZN's fleet consists of just 11 vessels and New Zealand has one of the largest exclusive economic zones in the world, the achievement of that aim is extremely challenging. The RNZN is expected to conduct a wide range of tasks from combat to customs patrols and also needs to be interoperable with other regional players such as Australia and the US. The RNZN is a credible small navy and is generally effective in the roles that it undertakes, but given the projected increase in security challenges that the service is expected to face, it can be argued that the triangular factors of strategic objectives, defence capabilities and defence resources in New Zealand are currently out of synch. New Zealand is an inherently maritime nation and the RNZN is central to both its security and prosperity. It is essential that further investment is committed to the RNZN in order to enable it to fulfil all of the tasks expected of it and to ensure that it can achieve its aim to be the 'best small nation navy'.